Analisis Kebutuhan Pegawai Kantor Urusan Agama Kecamatan di Sumatera Barat - M. Agus Noorbani (Direktorat Jenderal Bimbingan Masyarakat Islam, 2017)
The District Office of Religious Affairs (KUA) is a technical implementary unit (UPT) of the Directorate General of Community Guidance (Ditjen Bimas) Islam Ministry of Religious Affairs that has the duty to carry out the service and guidance of the Islamic community at the sub-district level in its working area. In carrying out its duties, the KUA organizes nine job functions, as set forth in the Regulation of the Minister of Religious Affairs number 34 of 2016 (PMA 34 2016) on the Organization and Working Procedures of The District Office of Religious Affairs. After the Presidential Regulation promulgation No. 48 of 2014 on Amendment to Government Regulation No. 47/2004, the marriage events number within KUA during the day and working hours in West Sumatra has increased sharply. Using a qualitative evaluation, this study attempted to examine the ideal needs of personnel in the KUA District. The results of this study found that most of the research areas still require additional staff to support the KUA District improvement service. The employees greatest needs are in the extension officers and executive staff group. Kantor Urusan Agama (KUA) Kecamatan merupakan unit pelaksana teknis (UPT) Direktorat Jenderal Bimbingan Masyarakat (Ditjen Bimas) Islam Kementerian Agama yang memiliki tugas melaksanakan layanan dan bimbingan masyarakat Islam pada tingkat kecamatan di wilayah kerjanya. Dalam melaksanakan tugasnya, KUA menyelenggarakan sembilan fungsi pekerjaan, seperti tertuang dalam Peraturan Menteri Agama nomor 34 tahun 2016 (PMA 34 2016) tentang Organisasi dan Tata Kerja Kantor Urusan Agama Kecamatan. Pasca diundangkannya Peraturan Presiden Nomor 48 tahun 2014 tentang Perubahan Atas Peraturan Pemerintah Nomor 47 Tahun 2004, jumlah peristiwa nikah di dalam KUA pada hari dan jam kerja di Sumatera Barat mengalami peningkatan tajam. Menggunakan kajian evaluasi kualitatif, kajian ini berusaha menelaah kebutuhan ideal tenaga pegawai pada KUA Kecamatan. Hasil kajian ini mendapati bahwa sebagian besar wilayah penelitian masih membutuhkan tambahan pegawai untuk mendukung peningkatan pelayanan KUA Kecamatan. Kebutuhan terbesar pegawai terdapat pada kelompok jabatan penyuluh dan tenaga pelaksana.